TINJAUAN HUKUM ACARA PERDATA TERHADAP PENGAMBILAN KETERANGAN SAKSI DI PENGADILAN AGAMA ( STUDI KASUS DI PA KABUPATEN MALANG ) - Usamah Salim Bob Said; Ahmad Subekti; Syamsu Madyan (Jurnal Hikmatina, 2020)
AbstractThis writing is motivated after reviewing the divorce case trial process in the religious court. when the judge calls two witnesses as evidence in the case of divorce simultaneously, but there are some judges who do not approve the matter of calling two witnesses together. So from the findings the authors found there were differences between the positive law in force regarding the procedure for hearing or taking witness statements in religious courts, especially in Malang district religious courts.The method  in this research is field research. This study aims to study intensively about the background and is carried out by going directly to the field to explore the data needed. The results of this study explain the ability to collect witnesses' information simultaneously. In general, the Panel of Judges is bound by legal evidence that is regulated in the Act. The evidence in accordance with the provisions of the Indonesian Civil Procedure Code. Among others: (1) evidence of letters (2) evidence of witnesses (3) evidence of alleged or prejudice (4) evidence of oaths. The law in theory is generally different in practice. The law is no longer as understood, which is more in accordance with its scope.Keywords: witness, religious court.